2005
DOI: 10.1287/mnsc.1040.0329
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Auction Mechanisms for Supply Chain Procurement

Abstract: We consider multiunit Vickrey auctions for procurement in supply chain settings. This is the first paper that incorporates transportation costs into auctions in a complex supply network. We first introduce an auction mechanism that makes simultaneous production and transportation decisions so that the total supply chain cost is minimized and induces truth telling from the suppliers. Numerical study shows that considerable supply chain cost savings can be achieved if production and transportation costs are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 21 publications
0
51
0
1
Order By: Relevance
“…Although some attention was given to auctions or procurement in such domains, (for example for forming supply chains [5] or procurement tasks [26]), previous work gave little attention to coalitional aspects. One exception is [60], which studies stability in supply chains, but focuses on pair coalitions and situations without side payments.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…Although some attention was given to auctions or procurement in such domains, (for example for forming supply chains [5] or procurement tasks [26]), previous work gave little attention to coalitional aspects. One exception is [60], which studies stability in supply chains, but focuses on pair coalitions and situations without side payments.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
“…One substantial and well-documented use of computational mechanisms falls under the general heading of -ecommerce.‖ For example, it has been reported that over 98% of Google's $6.14 billion in revenue (as of 2006) is achieved through the use of an explicitly designed auction mechanism for allocating advertising space on web pages returned from keyword searches [Edelman 2007]. Another substantial application area in electronic commerce is in supply chain optimization [Staib 2001, Chen 2005, Sandholm 2006]. …”
Section: Computational Mechanism Designmentioning
confidence: 99%
“…A first step in incorporating these other cost components while making a strategic sourcing decision is taken by Chen, Janakiraman, Roundy, and Zhang [59]. They provide the design of single item, multi-unit auction mechanisms that achieve overall supply chain efficiency while taking into account production and transportation costs.…”
Section: Single Item Multi-unit Procurement To Minimize Total Cosmentioning
confidence: 99%
“…Chen, Janakiraman, Roundy, and Zhang [59] present three separate auction mechanisms -Auction T, Auction R, and Auction S. The first two mechanisms incorporate transportation costs explicitly whereas in the third model, only production costs are considered for the allocation decision and transportation decisions are made subsequently. This provides a means to compare the two approaches and the implications for total cost of procurement strategies.…”
Section: Single Item Multi-unit Procurement To Minimize Total Cosmentioning
confidence: 99%
See 1 more Smart Citation